1979
DOI: 10.1021/ac50037a031
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme collagen membrane for electrochemical determination of glucose

Abstract: International audienceA new trace glucose analyzer has been designed using electrochemical sensors. The differential device includes (a) a glucose sensor consisting of a modified gas electrode in which ihe pH detector was replaced by a platinum disk and the porous film by a collagen membrane on which beta-D-glucose oxidase has been covalently bound after an acyl-azide activation process; (b) a compensating electrode mounted with a nonenzymatic collagen membrane. After injection of a glucose containing sample i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(45 citation statements)
references
References 9 publications
5
40
0
Order By: Relevance
“…The operational stability of enzyme electrodes [3,13] is among the most frequently studied analytical parameter [14], while for storage stability only a few studies were achieved [15][16][17] because of the need of intermittent measurements which require long time periods. Therefore, the predictive determination of enzyme electrode activity, based on an artificial thermal aging, could be considered as an attractive method because it permits a rapid estimation of biosensor shelf-life.…”
Section: Resultsmentioning
confidence: 99%
“…The operational stability of enzyme electrodes [3,13] is among the most frequently studied analytical parameter [14], while for storage stability only a few studies were achieved [15][16][17] because of the need of intermittent measurements which require long time periods. Therefore, the predictive determination of enzyme electrode activity, based on an artificial thermal aging, could be considered as an attractive method because it permits a rapid estimation of biosensor shelf-life.…”
Section: Resultsmentioning
confidence: 99%
“…The correlation of the values ob- previous study, we found that the surface enzyme activities of glucose-oxidase membranes, which ranged from 8 to 80 mU/cm 2 in 0.1 M glucose, gave steady-state responses proportional to these activities. 6 Thus, the sole calibration of this glucose electrode, i.e., AI/AC, is a good way to monitor the surface activity of such glucose-oxidase membranes. Initially, all membranes were stored at 4°C before or between tests at 30°C.…”
Section: Methodsmentioning
confidence: 99%
“…Enzymes have been first immobilized on collagen membranes through acylazide groups and used for the design of a selfcontained glucose electrode [6]. More recently, new types of polyamide ~upp01-t~ from Pall Industry S.A., France were selected to prepare bioactive membranes efficiently with a better reproducibility.…”
Section: Ho Detection-based Enzyme Electrodesmentioning
confidence: 99%
“…can be oxidized, yielding an undesirable output current and biased results. This can be overcome by a differential measurement with a twoelecrode system [6]. The two electrodes are equipped with the same type of membrane but the active electrode bears the grafted glucose oxidase whereas a plain membrane without enzyme is attached to the compensating electrode.…”
Section: Difirential Monitoringmentioning
confidence: 99%